Rare Case of Spinal Neurosarcoidosis with Concomitant Epidural Lipomatosis - Nesreen Jaafar; Maria Khoueiry; Samia J. Khoury; Achraf Makki (Case Reports in Neurological Medicine)
Introduction. Spinal neurosarcoidosis is a rare disease that can manifest as myelopathy, radiculopathy, or cauda equine syndrome. Spinal epidural lipomatosis is also a rare condition resulting from overgrowth of epidural fat tissue causing compressive myelopathy. To our knowledge, there are no reports linking epidural lipomatosis and spinal neurosarcoidosis. Case Report. We describe a case of progressive myelitis in the presence of concomitant spinal neurosarcoidosis and epidural lipomatosis which was a challenging diagnosis with complete response to treatment after addressing both diseases. Both etiologies are inflammatory in nature and share similar expression of inflammatory factors such as TNF-α and IL-1β. Conclusion. The common inflammatory process involved in these two diseases might explain a pathophysiological interconnection between both diseases that may underlie their concomitant development in our patient. If these two diseases are interconnected, in their pathophysiological mechanism remains a hypothesis that will need further investigation.